Clinical Presentation of Acute Ruptured Sinus of Valsalva Aneurysm as a Mimic of Acute Coronary Syndrome - Gaurav Jain; Kothandam Sivakumar; Zeeshan Ahmed Mumtaz (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging, 2022)
Acute ruptured sinus of Valsalva aneurysm may present with chest pain and rapidly worsening dyspnea. A 41-year-old male without known atherosclerotic risk factors presented with ST-segment elevation in leads aVR and V1 on electrocardiogram and elevated cardiac troponins and was diagnosed as acute coronary syndrome. After antiplatelet loading, statin, and heparin, he was referred due to worsening hypotension and tachycardia. Clinical examination and echocardiogram was challenging in the acutely dyspneic restless patient. Transesophageal echocardiography delineated the ruptured aneurysm and assisted in its management. Importance of physical examination and echocardiography in the emergency room is highlighted as manifestations may be varied.